(untitled) (Research, Society and Development, 2020)
This article aimed to analyze professional training studies at a higher level in its different levels and areas, based on self-efficacy investigations from the perspective of Social Cognitive Theory (TSC), which adds that each individual in his actions can be both cause and result of the their social extracts. In this, the theory admits that people can exert influence on their acts and actions, postulating that a large part of human behavior is determined by interactions with the environment and other individuals. Therefore, people are vectors of the events that involve them, but they do not determine the events that occur (Bandura, 1986). This research has a quantitative and qualitative approach, using the literature review technique. The sources were scientific articles, searched in search directories such as: CAPES, SCIELO, LILACS, and after applying the inclusion criteria, 13 articles could be selected. It can be seen that the articles on the theme Self-efficacy in Vocational Training were published from 2008 to 2019, with a higher frequency of publications in the last 4 years. Most articles use a quantitative approach, with the application of scales and questionnaires. The themes most related to Self-efficacy were: Professional Development (f = 4), Cognitive Social Theory (f = 3), Professional Guidance (f = 3), and Psychological Assessment (f = 3). Other themes also appeared less frequently, such as: well-being, internet and employability. However, it is important that this theme is further developed, investigating, for example, the actions and implications of self-efficacy at different levels of professional life.